UPAYA MENINGKATKAN HASIL BELAJAR IPA MELALUI PENDEKATAN KONTEKSTUAL DI KELAS VI SD NEGERI 018 KUBANG JAYA KECAMATAN SIAK HULU KABUPATEN KAMPAR - Zulhamdi Zulhamdi (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research is based on the result of science learning of grade VI students of SD Negeri 018 Kubang JayaKecamatan Siak Hulu Kabupaten Kampar which is still very low. This study aims to improve science learningoutcomes. From the data analysis, there was an increase of both teacher activity, student activity, and studentlearning result. The teacher activity at the 1st cycle meeting percentage was 70% (good) and at the 2nd meetingincreased 5% to 75% (good). In the second cycle of the meeting 3 teacher activities increased 10% from 75%(good) to 85% (very good) and at meeting 4 increased 10% from 85% (very good) to 95% (very good). Judgingfrom the student activity also increased from the 1st meeting of cycle I was 65% (enough) and at meeting 2increased 15% to 80% (good). In the second cycle of meeting 3 it increases 5% from 80% (good) to 85% (verygood) and at meeting 4 increases 10% from 85% (very good) to 95% (very good). Judging from the results of thestudents also experienced preningkat, from the average score of students on a basic score of 62.78. after the firstcycle the student's average score increased to 79.44 with an increase of 16.66 points from the baseline score. Inthe second cycle student learning outcomes also increased as much as 11.67 points from cycle I with averagestudent's grade 91.11. From the data analysis there is an increase both from teacher activity, student activity,and student learning outcomes. It can be concluded that the advancement of contextual learning can improve thelearning outcomes of science students of grade 6 of SD Negeri 018 Kubang Jaya Kecamatan Siak HuluKabupaten Kampar.